PENGEMBANGAN SUMBER DAYA MANUSIA BERBASIS TOTAL QUALITY MANAGEMENT DI SMK MUHAMMADIYAH PRAMBANAN - Erlina Yuliyati (JURNAL AL-TANZIM, 2020)
This paper presents the development of human resources based on total quality management conducted at SMK Muhammadiyah Prambanan. Total quality management is an approach offered, so that educational institutions can survive and be able to win the competition between existing institutions. This research uses a qualitative approach with case study. The technique of collecting data is done through; observation, interview and documentation. Research data are presented in narrative descriptive form. The results showed that; SMK Muhammadiyah Prambanan implements several stages in human resource management, namely; planning, recruitment, and development of human resources that are carried out in a planned, systematic and oriented towards continuous quality improvement. Through the implementation of total quality management, "SMK Muhammadiyah Prambanan" managed to become a superior school and gain the trust of the public.